The efficacy of Tiamulin hydrogen fumarat 10% in the feed to prevent chronic respiratory disease in broiler chickens - Soeripto . (Indonesian Center for Animal Research and Development (ICARD), 2008)
Up to presence chronic respiratory disease (CRD) of chickens is still causing economic losses against poultry industries in the world. The purpose of this trial is to determine the efficacy and safety of a compatible dose of Tiamulin hydrogen fumarat 10% in combination with monensin for the control of CRD in broilers. A number of 630 day-old broilers were divided into 3 groups and each group was divided again into 7 subgroups of 30 equally sexed birds. Each subgroup was placed randomly in 2 chicken houses. Up to 3 weeks of age, chickens in Group I were fed with starter feed (SP1) containing 100 ppm monensin only without other treatment and used as control. Chickens in Group II were fed with SP1 feed containing 30 ppm Tiamulin hydrogen fumarat (3 – 6 mg/ kg BW) and 110 ppm amoxicillin, this feed is called SP1+, whereas chickens in Group III were administered with SP1 feed and treated with enrofloxacin liquid formulation 10% with a dose 0.5ml/L in drinking water for the first 5 days of life. Started from 22nd day until the end of the experiment at 32 days of age, all chickens in Groups I, II and III were fed with SP2 finisher feed containing neither monensin nor Tiamulin hydrogen fumarat. The results of the experiment showed that no statistical difference in bodyweight and feed conversions among the groups at 32 days of age but feed conversion in Group II was statistically different compared to those in Groups I and III at week 2. No clinical signs of toxic interaction of monensin combined with Tiamulin were observed. Lesions of airsacculitis and ascites occurred only in dead chickens of Groups I and III but not in chickens of Group II. The incidence of pneumonia in Group I occurred in all dead birds which is statistically different to Group II that had one lesion of pneumonia. Mycoplasma gallisepticum and Escherichia coli organisms were able to be isolated from the chickens that had pneumonia and ascites in Groups I and III only. The results of the experiment showed that combination of 30ppm Tiamulin hydrogen fumarat + 110 ppm amoxicillin is effective for preventing CRD in broilers and save if it is combined with 100 ppm monensin. Key Words: Tiamulin Hydrogen Fumarat, Chronic Respiratory Disease, Broilers